Sistem Informasi Manajemen Persediaan Obat Berbasis Web Menggunakan Metode Prototype Pada Apotek - Krisna Ruliyanto; Septi Andryana; Aris Gunaryati (Universitas Indraprasta PGRI Jakarta, 2021)
Management plays a very important role in supporting the running of the asset inventory and its management. Currently, the drug supply asset management system at the Kaka Bekasi Pharmacy is still carried out using a simple computerized method, namely using the Microsoft Excel application and manual recording, causing various kinds of problems. The problem faced by the pharmacy is that the asset management of drug supplies in the process of recording orders, purchases, sales is not recorded accurately and is well integrated so that in the search process one has to look for drug stock data, as well as being slow in knowing which drugs will expire. Lack of security in the system is also a problem with pharmacies as it can be accessed by anyone. Therefore, to assist managers in drug asset management, a Web-based Drug Inventory Asset Management Information System was designed using the Prototype Method at the Kaka Bekasi Pharmacy, system design using UML, PHP programming language with sublime text editor and MySQL database management software. The result of this research is a prototype that can be further developed in order to produce an asset management information system that can be implemented at the Kaka Bekasi Pharmacy.